PARENTING EDUCATION GUNA MENINGKATKAN PARENTING SELF-EFFICACY PADA ORANG TUA DARI ANAK DENGAN GANGGUAN AUTISME - Ekaningtyas, Ni Luh Drajati (PRATAMA WIDYA : JURNAL PENDIDIKAN ANAK USIA DINI, 2019)
Parents of children with autism disorder faces many challenges and psychological burdens which can cause stress and depression that can affect parenting quality given to the children. Hence, the ideal amount of parenting self-efficacy is needed in order to overcome stressors related to parenting. Parenting education in a form of psychoeducation can be used to create and improve parenting self-efficacy by establishing/intensifying perceptions and increasing the parent’s cognitive or understanding regarding parenting strategy of children with autism disorder.